2022
DOI: 10.1053/j.jvca.2021.11.032
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Multidisciplinary Follow-Up of Patients With COVID-19 Requiring Invasive Mechanical Ventilation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 71 publications
0
36
1
Order By: Relevance
“…Although several prospective studies have sought to examine long‐term CT changes in COVID‐19, these findings were limited by small cohort sizes 6,8–21 . In addition, the interpretations of each study varied due to the wide range of severity.…”
Section: Introductionmentioning
confidence: 99%
“…Although several prospective studies have sought to examine long‐term CT changes in COVID‐19, these findings were limited by small cohort sizes 6,8–21 . In addition, the interpretations of each study varied due to the wide range of severity.…”
Section: Introductionmentioning
confidence: 99%
“…Although COVID-19 patients benefit from in-hospital rehabilitation [4], most patients do not qualify for this. Studies have shown promising results in recovery from COVID-19 [5,6], whereas others point out that some groups may still suffer from persisting respiratory impairments [7] and have low participation in society [8]. In-hospital care for COVID-19 has also been suggested to be a predictor of long sick leave [9].…”
Section: Introductionmentioning
confidence: 99%
“…Zangrillo et al 17 group applied a validated EuroQol Group EQ-5D-3L questionnaire in a follow-up of a small sample of patients (56) but found a smaller prevalence of post-COVID-19 symptoms in the 1-year follow-up, not distinguishing the symptoms time length.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term, computed tomography images and other pulmonary sequelae were not evaluated in this study and will be the next steps. 16 , 17 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%